Davids still exist among Goliaths: a story of modest self-access centre establishment and survival in times of economic decline - Papadima-Sophocleous, Salomi (My University, 2013)
In a university setting, self-access language learning centres (SALLC)s are generally created out of the need to support students and other members of the university and extra-mural community to explore and expand their language learning horizons. The nature of SALLCs depends on the needs of each institution and its community. They range from fully self-directed to semi-guided, from virtual online-self-access centres (OSAC)s to real centres, with traditional print, and more contemporary electronic and digital materials. While much of the research so far has dealt with different aspects of SALLCs, particularly of prominent ones, this article reports on the case of a small-scale SALLC, which was designed and developed, and which has operated, during difficult circumstances. This report describes how despite the administrative and financial constraints faced during the establishment of the host university and language centre, current theories and practices in SALLC were still taken into account. Also, despite these difficulties and the economic constraints being endured by the country as a whole, a number of strategies were implemented enabling the SALLC to be accessible to all students, with a view to promoting both autonomy and lifelong learning. The data used consisted of field notes collected during the period of operation as well as results from an evaluation of the use of different learning pathways on offer. Finally, the challenges still being faced as the SALLC enters a new period in its development are outlined.
Keywords: Modest SALLC design; Operational constraints; Learning pathways; Promoting autonomy